Ujęcie definicyjne controllingu w niemieckim obszarze językowym - Karwacki, Piotr (Definitions of Controlling in German-Speaking Countries, 2008)
The author of the article provides definitions of controlling in German speaking countries. Literature research of the subject allowed the author to make a general analysis of controlling including its features in German speaking regions as well as to define the trends of its development. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 75-83